Developing Sharing Breastmilk Program : Survey Communities toward Intention in Breastmilk Donor Practice - Krisdiana Wijayanti; Murti Ani; Novita Ika Wardani (Universitas Aisyah Pringsewu, 2023)
Not all mothers can breastfeed directly or provide sufficient breast milk to their babies. This condition makes a sharing breastmilk become one of solution to fullfill the baby need in breastmilk. The purpose of this study was to survey the public's knowledge and intention to donate breast milk or receive breast milk donors. The research design used an analytical survey with the general population being man and women of productive age (less than 20 years). The sampling technique used survey sampling, with a sample of 140 respondent’s. Measurement of knowledge and intension using pre and post-questionnaires after the respondents participated in the mini-workshop sharing breast milk milk in persective of religion, humanism and health. Data was analized using paired t-test. The result of the knowledge test was p=0.003 (p less than 0.05), the intention test were p = 0.043 (p less than 0.05), which means that there was a difference between pre and post mother's knowledge and intention after attending a mini-workshop. The survey results showed that there is an increase in interest when respondents are given knowledge become the basis for doing second phase of research, which is Study Management in Breastmilk Bank di Dr. Jose Fabella Memorial Hospital Philippines dan Lactashare Malang Indonesia. Abstrak: Tidak semua ibu dapat memberikan ASI secara langsung atau memberikan cukup ASI kepada bayinya. Kondisi ini membuat program berbagi ASI menjadi salah satu solusi untuk memnuhi kebutuhan bayi akan ASI melalui penyediaan ASI donor. Tujuan penelitian ini adalah mengetahui pengetahuan dan minat masyarakat untuk mendonorkan ASI atau menerima ASI donor. Desain penelitian menggunakan survey analitik dengan populasi adalah masyarakat umum laki laki maupun perempuan usia produktif (kurang dari 20 tahun). Teknik sampling menggunakan survey sampling, dengan jumlah sampel 140 respondent. Pengukuran pengetahuan dan minat menggunakan kuisioner pre dan post setelah responden mengikuti kegiatan mini woskhop tentang berbagi ASI dalam perspektif agama, humanisme dan kesehatan. Analisis data penelitian menggunakan uji paired t-test. Hasil uji pengetahuan p=0,003 (p kurang dari 0,05), minat p=0,043 (p kurang dari 0,05), yang berarti ada beda pre dan post pengetahuan dan minat setelah mengikuti mini workshop berbagi ASI. Hasil survei yang menunjukkan ada peningkatan minat ketika responden diberikan pengetahuan menjadi dasar peneliti melanjutkan penelitian tahap kedua, yaitu Studi Manajemen di Breastmilk Bank di Dr. Jose Fabella Memorial Hospital Philippines dan Lactashare Malang Indonesia